2006
DOI: 10.1002/pa.35
|View full text |Cite
|
Sign up to set email alerts
|

No news is good news? Press coverage and corporate public affairs management

Abstract: Being in the public eye puts pressure on an organization's Public Affairs (PA) function. This study finds that firms more closely covered by the press tend to be more forceful in promoting their own position on social issues (social buffering). Press coverage is not associated with greater corporate efforts to comply with societal expectation (social bridging). Overall, press coverage is weakly associated with lowered perceived corporate public affairs performance. Copyright © 2006 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
(25 reference statements)
0
6
2
Order By: Relevance
“…They found that environmental legitimacy demonstrated a nonlinear relationship with disclosure because companies employed impression management strategies to influence external perceptions. Fourth, the visibility results in this study differ from those found by Meznar and Nigh (1995) and Meznar et al (2006), who did not find significant relationships between visibility and company behavior. Our visibility variables, however, were more extensive in that different types of visibility (general/issue related) and Internet news sources were also incorporated into the visibility measure.…”
Section: Overview and Contributionscontrasting
confidence: 73%
See 3 more Smart Citations
“…They found that environmental legitimacy demonstrated a nonlinear relationship with disclosure because companies employed impression management strategies to influence external perceptions. Fourth, the visibility results in this study differ from those found by Meznar and Nigh (1995) and Meznar et al (2006), who did not find significant relationships between visibility and company behavior. Our visibility variables, however, were more extensive in that different types of visibility (general/issue related) and Internet news sources were also incorporated into the visibility measure.…”
Section: Overview and Contributionscontrasting
confidence: 73%
“…We totaled the scores for each company and averaged the stories over a 2-year period in order to mitigate the impact of events in 1 year dramatically affecting the scores. Meznar et al (2006) have noted that with the 24-h news cycle, Internet blogs, e-zines, and other electronic information sources, print media coverage alone is a deficient indicator of media visibility. The Google News Archive differs from the general Google search engine in that it crawls stories from web sites including newspaper publishers and aggregators to cover a vast number of issues and perspectives.…”
Section: General Visibilitymentioning
confidence: 97%
See 2 more Smart Citations
“…According to Pfeffer and Salancik (1978), visibility affects the level of outside pressure a firm experiences because stakeholders take greater interest in firms that are visible. Meznar et al (2006) found that press coverage was positively associated with firms' attempts to shape the way outsiders perceived the firm and/or the issue. Stakeholders' demands for compliance create institutional pressures (Maignan and Ferrell, 2001), and the media exacerbate these pressures by focusing public attention on corporate behavior (Chen and Meindl, 1991;Erfle et al, 1990).…”
Section: The Role Of Visibilitymentioning
confidence: 97%